Development of a Smartphone Application for Dietary Self-Monitoring - Ahn, Jeong Sun; Kim, Dong Woo; Kim, Jiae; Park, Haemin; Lee, Jung Eun (Frontiers in Nutrition, 2019)
This article describes the key features of the Well-D, a mobile dietary self-monitoring application developed to assess and track dietary intake. To test the acceptability of the app, 102 adults aged 18 years or older were asked to use Well-D for 3 days or more. After using the app, they recorded their likes/dislikes and recommendations regarding ways to improve Well-D. A mobile application for dietary assessment and monitoring may have the potential to help individuals and groups to engage in healthy behaviors.